Students' Algebraic Thinking Process Based On Reflective And Impulsive Cognitive Styles - Nur Wiji Sholikin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Algebraic thinking is very important because it helps students expand their thinking in solving concrete problems through the ability to identify patterns, recognize relationships between mathematical elements, and understand the structure of a problem. This study aims to analyze the differences in students' algebraic thinking process abilities based on reflective and impulsive cognitive styles. The research method used is a descriptive quantitative method. The subjects of the study were 27 high school students in grade 10. The instruments used in this study consisted of Matching Familiar Figure Test (MFFT) cognitive style test questions, algebra ability test questions, and interview guidelines. The data analysis technique in this study used data triangulation. The results of the analysis showed that students with a reflective cognitive style had an average algebra score of 84 and showed more consistent performance, compared to impulsive students who had an average score of 67. Interview findings supported the quantitative results, where reflective students tended to be thorough, focused on understanding concepts, and careful in solving problems, while impulsive students worked on problems quickly but lacked analysis, resulting in more frequent technical errors. This data triangulation confirmed that cognitive style had a significant effect on students' thinking and performance in solving algebra problems. This study recommends the application of Polya's step-based problem-based learning method for reflective students and game-based learning with self-monitoring strategy for impulsive students as an effort to improve mathematical problem-solving abilities.